Bedside medication delivery programs: suggestions for systematic evaluation and reporting. (4th May 2019) - Agarwal, Parul; Poeran, Jashvant; Meyer, Joanne; Rogers, Linda; Reich, David L; Mazumdar, Madhu
Abstract: Purpose: Several factors lead to medication non-adherence after hospital discharge. Hospitals and pharmacies have implemented bedside medication delivery (BMD) programs for patients, in an attempt to reduce barriers and improve medication adherence. Here, we provide a critical review of the literature on these programs. Data sources: We conducted a literature search on BMD programs in PubMed, Google Scholar, Scopus and a general Google search using these keywords: 'medication delivery bedside', 'discharge medication delivery', 'meds to bedside' and 'meds to beds'. Study selection: We identified 10 reports and include data from all reports. Data extraction: Data on study characteristics and settings were extracted along with four outcomes: medication error, patient satisfaction, 30-day hospital readmission and visits to the emergency department. Results of data synthesis: Of the 10 reports, only 4 were peer-reviewed publications; others were reported in the lay press. Outcomes were reported in both qualitative and quantitative terms. Less than half of reports provided quantitative data on 30-day readmission and patient satisfaction. Others suggested qualitative improvement in these outcomes but did not provide data or specific details. None reported outcomes of their programs beyond 30 days. Conclusion: We highlight the need for increased use of optimal program design and more rigorous evaluations of the impact of BMD programs. We also provide guidelines on the types of evaluations that are likely needed and encourage improved reporting.